Sex differences in subjective and objective responses to a stimulant medication (methylphenidate): Comparisons between overweight/obese adults with and without binge‐eating disorder. Issue 5 (22nd December 2015) - Davis, Caroline; Levitan, Robert D.; Kaplan, Allan S.; Carter‐Major, Jacqueline C.; Kennedy, James L.
ABSTRACT: Objective: The purpose of this study was to examine sex differences in response to a single dose of a psychomotor‐stimulant medication (methylphenidate: MP) and to assess whether expected differences were moderated by binge‐eating disorder (BED) status. It is anticipated that findings will shed light on factors that contribute to response variation in the use of stimulant pharmacotherapy to treat BED. Method: The study employed a double‐blind, drug‐placebo, cross‐over design in overweight/obese adults with BED ( n = 90) and without BED ( n = 108). Emotional/mood ratings were assessed every 15 minutes after oral administration of the drug/placebo, and appetite, cravings, and consumption were assessed during a laboratory‐based snack‐food challenge. Results: Women reported earlier and more sustained "overall" effects of the drug—including "feeling high"—than the men. There was also a significantly greater suppression in appetite ratings, food cravings, and food consumption from the placebo to the drug condition among the women. Indeed, among men there were no significant differences between the two conditions on any of the food‐related variables. BED status also did not moderate any of the drug‐placebo differences. Discussion: These findings are relevant to the use of stimulant pharmacotherapy for BED, and raise the possibility that overweight/obese men may be relatively less responsive to this form of treatment. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:473–481).